2007
DOI: 10.1007/s10669-007-9076-x
|View full text |Cite
|
Sign up to set email alerts
|

The bioeffects of extremely weak power-frequency alternating magnetic fields

Abstract: We report the results of a study of the influence of extremely-weak alternating magnetic fields (EW AMF) directed co-linearly to the static Earth's magnetic field on the rate of regeneration in planarians and also on the rate of gravitropic response in the stem segments of flax. In particular we obtained the data on the dependence of the value of bioeffects on the amplitude (at fixed 60 Hz-frequency) and on the frequency (at fixed 1.6 lT-amplitude) of the alternating component. Our data show unambiguously that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Only a few studies of EMF effects on plants [Tkalec et al, 2005[Tkalec et al, ,2007[Tkalec et al, ,2009Sharma et al, 2009] have been reported. In early studies seeds were exposed to extremely low frequency (ELF) magnetic fields or RF radiation in order to investigate biological effects [Bigu-Del-Blanco et al, 1977;Belova and Lednev, 2001;Belova et al, 2007;Tkalec et al, 2009;Shine et al, 2011], however, the results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies of EMF effects on plants [Tkalec et al, 2005[Tkalec et al, ,2007[Tkalec et al, ,2009Sharma et al, 2009] have been reported. In early studies seeds were exposed to extremely low frequency (ELF) magnetic fields or RF radiation in order to investigate biological effects [Bigu-Del-Blanco et al, 1977;Belova and Lednev, 2001;Belova et al, 2007;Tkalec et al, 2009;Shine et al, 2011], however, the results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Most experiments devoted to the effect of weak combined alternating (AC) and static (DC) magnetic fields (MFs) on biosystems have been performed using fields with the amplitude of the AC component of tens of microteslas against the background of the static MF of comparable strength. However, there is substantial evidence indicating that very weak alternating MFs of the nanotesla range are also capable of inducing marked biological effects [Juutilainen et al, 1987;Berman et al, 1990;Liburdy et al, 1993;Novikov et al, 1996Novikov et al, , 2005Novikov et al, , 2008Persinger et al, 1999;Belova and Lednev, 2001;Blackman et al, 2001;Novikov, 2004;Bobkova et al, 2005;Belova et al, 2007]. It should be noted that in the majority of cases, the experiments with very weak AC MFs were conducted against the background of the geomagnetic field whose magnetic flux density is $50 mT.…”
Section: Introductionmentioning
confidence: 99%
“…Belova et al (2007) paid a special attention on the biological effects of alternating magnetic fields originated from natural and technogenic sources. The spectrum of the effects of lowintensity magnetic field could be extended with the paper of Abdolmaleki et al (2007) who discussed the role of static magnetic fields on cell death.…”
Section: Chernobyl and Fukushimamentioning
confidence: 99%